Overexpression of KH-type splicing regulatory protein regulates proliferation, migration, and implantation ability of osteosarcoma - Dumnoensun Pruksakorn (2018)
Osteosarcoma is a common malignant bone tumor in children and adolescents. The current 5-year survival rate is ~60% and that seems to be reaching a plateau. In order to improve treatment outcomes of osteosarcoma, a better understanding of tumorigenesis and underlying molecular mechanisms is required for searching out possible new treatment targets. This study aimed to identify the potential proteins involving the pathogenesis of osteosarcoma using a proteomics approach. Proteins extracted from primary cell culture of osteosarcoma (n=7) and osteoblasts of cancellous bone (n=7) were studied. Using 2-DE based proteomics and LC-MS/MS analysis, we successfully determined seven differentially expressed protein spots. Four upregulated proteins and three downregulated proteins were observed in this study in which KH-type splicing regulatory protein (KSRP) was selected for further exploration. KSRP was significantly upregulated in osteosarcoma cells compared to osteoblasts using western blot assay. In addition, immunohistochemistry demonstrated that KSRP was also highly expressed in osteosarcoma tissue of independent cases from the experimental group. More importantly, KSRP silencing of osteosarcoma cell lines significantly decreased cell proliferation, migration ability, as well as implantation and growth ability in chick chorioallantoic membrane assay. Taken together, these findings demonstrate that KSRP plays important roles in regulatory controls of osteosarcoma pathogenesis and serves as a potentially therapeutic target of osteosarcoma.